Tipos de liderazgo en la gestión del talento humano bajo el marco de la cuarta revolución industrial (2021)
We are in a changing world and where industries are growing rapidly; additional to this, in a society with different generations with ideas that are more innovative, changing and strategic every day. The challenge for organizations is to find leaders and not bosses, people with the ability to mobilize their teams to achieve their objectives and grow. Since ancient times, the business world has had different types of command, long ago called headquarters today leadership, which have been changing markets, industries and have allowed the evolution of the human being.